The pivotal role of malic enzyme in enhancing oil accumulation in green microalga Chlorella pyrenoidosa. Issue 1 (December 2016) - Xue, Jiao; Wang, Lan; Zhang, Lin; Balamurugan, Srinivasan; Li, Da-Wei; Zeng, Hao; Yang, Wei-Dong; Liu, Jie-Sheng; Li, Hong-Ye
Abstract Background The fast growing photosynthetic microalgae have been widely used in aquaculture, food, health, and biofuels. Recent findings in the diatom has proposed a pivotal role of NADP-malic enzyme in generation of NADPH as an important supply of reducing power for fatty acid biosynthesis. To test the lipogenic malic enzyme for fatty acid synthesis in green algae, here the malic enzyme genePtME from the oleaginous diatomPhaeodactylum tricornutum was expressed in a representative green microalgaChlorella pyrenoidosa . Results The engineeredC. pyrenoidosa strain showed higher enzymatic activity of malic enzyme which subsequently promoted fatty acid synthesis. The neutral lipid content was significantly increased by up to 3.2-fold than wild type determined by Nile red staining, and total lipid content reached 40.9 % (dry cell weight). The engineered strain exhibited further lipid accumulation subjected to nitrogen deprivation condition. Upon nitrogen deprivation, engineered microalgae accumulated total lipid up to 58.7 % (dry cell weight), a 4.6-fold increase over the wild type cells under normal culture condition. At cellular level, increased volume and number of oil bodies were observed in the engineered microalgal cells. Conclusions These findings suggested that malic enzyme is a pivotal regulator in lipid accumulation in green microalgaC. pyrenoidosa, and presenting a breakthrough of generating ideal algal strains for algal nutrition and biofuels.